A SCOPING REVIEW OF THE EFFECTS OF MALL ON COLLEGE EFL LEARNERS’ ENGLISH LISTENING AND SPEAKING PERFORMANCE - Wang, Yanan; Soo, Ruey Shing (Universiti Selangor (UNISEL), Malaysia, 2024)
The integration of mobile-assisted language learning (MALL) has become increasingly prevalent in enhancing the English listening and speaking (ELS) skills of college-level English as a Foreign Language (EFL) learners. This scoping review aims to map out the existing research on the effects of MALL on the English listening and speaking performance of college EFL learners, identify key themes, and highlight gaps for future research. Studies focusing on college EFL learners, using MALL interventions, and measuring listening and speaking performance were included. A systematic search was conducted across databases including Scopus, ERIC and Web of Science. Data were charted and synthesized to identify patterns, themes, and research gaps. The review includes 33 studies, highlighting positive effects of MALL on listening and speaking skills, with variations in methodology, intervention duration, and assessment tools. It has been demonstrated that MALL has significant positive effects on both listening and speaking skills. In terms of listening skills, MALL has been found to improve learners’ listening comprehension, listening fluency, and vocabulary acquisition and recognition. In terms of speaking skills, MALL contributes to improving pronunciation, speaking fluency, lexical richness, speech production, and skills of presentation and communication. It also enhances presentation performance and communication skills. These findings highlight MALL’s potential in improving EFL learners’ listening and speaking performance, though more longitudinal and diverse studies are needed.